2021
DOI: 10.24191/ajue.v17i3.14525
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Orientations of Learning Japanese as A Foreign Language Among Undergraduates In A Public University In Malaysia

Abstract: Motivation is a key factor in learning a foreign language.  This study investigated the instrumental, integrative and attitudinal motivation level of students learning Japanese as a FL in a public university in Malaysia.  A survey questionnaire based on Gardner’s (1985) AMTB (Attitude/Motivation Test Battery) and Dornyei’s (1994) Attitudinal Motivation was given to 171 undergraduates.  Descriptive and Inferential statistics were used to analyse the data.  The results of the study indicated that the foreign lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
1
10
1
Order By: Relevance
“…Going deeper, the integrative motivation has been identified as the primary motivation to learn Japanese language (4.4508±0.7444), followed by instrumental motivation (3.7206±0.9991), and lastly attitudinal motivation (3.4476±1.0970). The survey results were mainly in-line with previous studies on motivation of learning foreign languages(Maktiar Singh et al, 2021;Teh et al, 2018). Then, ordinal logistic regression was performed to investigate the relationship between each motivation type to the interest to learn Japanese language.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Going deeper, the integrative motivation has been identified as the primary motivation to learn Japanese language (4.4508±0.7444), followed by instrumental motivation (3.7206±0.9991), and lastly attitudinal motivation (3.4476±1.0970). The survey results were mainly in-line with previous studies on motivation of learning foreign languages(Maktiar Singh et al, 2021;Teh et al, 2018). Then, ordinal logistic regression was performed to investigate the relationship between each motivation type to the interest to learn Japanese language.…”
supporting
confidence: 58%
“…Furthermore, numerous Malaysian universities have been offering foreign language such as Japanese, French, Spanish language courses as one of the non-credit subject or credited electives in their curriculums. In the Malaysian Education Blueprint 2015-2025 introduced by the Ministry of Higher Education, learning foreign language has been highlighted as one of the key components in driving Malaysia's vision to become a fully developed country (Maktiar Singh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Yean et al (2022), who explored learning Japanese online as a foreign language, mainly focused on the Three Phases of Motivation where it was discovered that students were most motivated during the pre-actional phase due to curiosity which has motivated them to learn intrinsically. Similarly, Singh et al (2021), who also examined learning Japanese online as a foreign language, namely investigated integrative and attitudinal motivational orientation and uncovered that students' levels of integrative and attitudinal motivation were equally high and slightly higher than instrumental motivation. Both researchers concluded that the interest and motivation of students to learn a foreign language were somewhat influenced by the instructors.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Little attention has been paid to understand how existing motivational theories can be adapted to optimize online learning and student engagement within technology-enabled learning contexts (Chiu et al, 2021). Through the studies by Yean (2022); Singh et al (2021), it is evident that triggered situational interest which comes from the social support, i.e., instructor support scaffolds the students' interest and motivation to learn foreign language online. External factors, on the other hand, play a role in demotivating students to learn online.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Researchers believe this might be due to challenges in collecting and analysing the spoken data. Notably, 86% of ESP research data is written, while only 14% is spoken, as highlighted by Maktiar Singh (2019) and Srinon and Sucharitrak (2020). Dudley (1998) points out that the scarcity of spoken data can be problematic, especially since speech is often more crucial in academic settings, such as lectures and seminars.…”
Section: Literature Reviewmentioning
confidence: 99%